Ecolodge sebagai Implementasi Pendidikan Sains (IPA) yang Multidimensi - Pauzi, Iswari; Sarjan, Muhammad; Muliadi, Agus; Azizi, Asrorul; Hamidi, Hamidi; Yamin, Muhammad; Muttaqin, Muh. Zaini Hasanul; Ardiansyah, Bakhtiar; Rahmatiah, Rindu; Sudirman, Sudirman; Rasyidi, Mulia; Khery, Yusran (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
Science Education (IPA) is a science related to systematic natural and material symptoms that are arranged regularly, generally in the form of a collection of observations and experiments. Science learning is expected to be a vehicle for students to learn about themselves and the surrounding nature, as well as the prospect of further development in applying it in everyday life. In the world of education, environmentally sound education has begun to be integrated, for example education with the vision of SETS (Science Environment Technology and Society) is defined as science, environment, technology, and society, is a unit that in the concept of education has implementation so that students have the ability to think higher (higher order thinking) Science, Technology and Society (STS) approach or the Science, Technology and Society (STM) approach. is a combination of concept approaches, process skills, CBSA, Inquiry and disambiguation as well as environmental approaches. One example of the implementation of the learning model with the environment is lodging in an open environment with an environmentally sound concept called ecolodge. Ecolodge is a small hotel or guesthouse that combines local architecture, culture and natural characteristics, supports environmental conservation by reducing waste and energy use and provides social and economic benefits to local communities.